The solvent extraction and separation of the tetrachloroplatinate (2) and -palladate (2) ions in the presence of stannous chloride into methylisobutylketone - Ahmed, Nazir (Department of Chemistry, 2023)
The potentialities of extracting platinum(!!) and palladium(II) selectively as complexes of [M(SnCl3)nCl4-nJ2 - (M=Pt,Pd) was examined. A study was made of the effect of SnCl2 on the solvent extraction of K2PtCl4 and K2PdCl4 from solutions containing various concentrations of HCL into methylisobutylketone (MIBK) /hexane mixtures. It was found that increasing SnCl2 concentrations dramatically increases the efficiency of extraction of platinum into the organic phase. In the presence of a five-molar excess of SnCl2, platinum is quantitatively extracted. In contrast, palladium is not quantitatively extracted under similar conditions. Our studies show that the percentage extraction of platinum and palladium depends upon the Sn(II) :M(II) ratio, the HCL, H+ and c1- concentrations and the equilibration time as well. Studies were also carried out to investigate the possibility of separating platinum and palladium by varying the amount of SnCl2 present. Results obtained showed that the separation was dependant on the HCL concentration of the aqueous phase and the composition of the organic phase. The effects of macro amounts of palladium and excess tin on the separation process was also examined. A preliminary study of the effect of four base metals on the separation was undertaken.